DINAMIKA PERKEMBANGAN HUKUM DALAM KEHIDUPAN BERMASYARAKAT - Leoni Ayu Pratiwi; Elfrida Ratnawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2023)
Community development (change) is usually identified with development. Generally people think that development is a neutral noun which means a word used to describe processes and efforts to improve economic, political, cultural life, community infrastructure, and so on. With such an understanding, development is equated with the word